Human rhinosporidiosis: still an elusive disease - Swain, Santosh Kumar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Rhinosporidiosis is a granulomatous infection of the mucous membrane caused by Rhinosporidium seeberi. It usually affects the nasal and nasopharyngeal mucosa but sometimes involve extra-nasal sites such as lips, buccal mucosa, palate, larynx, trachea, lacrimal sac, skin, scalp, penis, urethra, vulva and bone. The natural habitat of this organism is water and the infection probably spreads via trans-epithelial penetration. Histopathological examination confirms the diagnosis. The treatment of choice is complete surgical excision with cauterization of the base but the medical treatment shows limited efficacy. The patient of disseminated rhinosporidosis does not respond to the conventional treatment such as surgical excision and dapsone and with amphotericin B also proved futile result. This infection is usually overlooked, despite R. seeberi being endemic in tropical country like India. Due to the negligence in the diagnosis and taxonomic enigma of rhinosporidiosis, here we discuss the details of its epidemiology, etiopathology, clinical presentations, diagnosis and current treatment. Because rhinosporidiosis is relatively rare, we hope this review article will serve as aid and guide to the medical community for helping further research.